Post‐release acclimation of translocated low‐elevation, non‐migratory bighorn sheep. (1st June 2014) - Clapp, Justin G.; Beck, Jeffrey L.; Gerow, Kenneth G.
ABSTRACT Use of global positioning system (GPS) transmitters provides opportunities to evaluate ecological questions associated with fine‐scale animal movements. One important application is to evaluate how animals acclimate to new surroundings after translocation. Our objective was to quantify temporal acclimation for low‐elevation, non‐migratory bighorn sheep (Ovis canadensis) from 3 translocations to the Seminoe Mountains in south‐central Wyoming, USA, from 2009 to 2010 (n = 38) as well as for bighorns captured and released on‐site in 2011 (n = 24). We used number of days for movements from individual bighorn to stabilize as a measure of acclimation. Mean acclimation for translocated bighorns after release was 29.3 days (SE = 2.5, range = 0–70). Mean acclimation for bighorns captured and released on‐site was 5.0 days (SE = 2.4, range = 0–52). Paired comparisons indicated acclimation for 16 previously translocated bighorns that were captured and released on‐site was reduced by 30.8 days (SE = 5.0) or 86%. Within translocation efforts, bighorn females in supplemental releases acclimated an average of 19.5 days sooner (or in 57% of the time) than animals from the first translocation. Because acclimation periods after translocation releases are associated with increased mortality risk, managers should consider supplemental releases to minimize acclimation periods. © 2014 The Wildlife Society.